HYDROTHERMAL ALTERATION AND MINERALIZATION OF THE PETROTA EPITHERMAL SYSTEMS (W.THRACE, GREECE) - Μιχαήλ Κ.; Δημήτρουλα Μ. (Bulletin of the Geological Society of Greece, 2004)
At the Petrota graben important epithermal zones are developed. On the basis of the mineral assemblages of alteration zones and the type of the host rocks, the epithermal zones can be grouped into three epithermal systems: 1. Perama epithermal system 2. Mavrokoryfi epithermal system and 3. Othondoto epithermal system Hydrothermal alteration zones are developed within volcanoclastic rocks - epiclastic sandstones, andésite tuffs (Perama epithermal system), hyaloclastites (Mavrokoryfi) and rhyolitic rocks (Othondoto). Silicification (in various types) and advanced argillic alteration are the most important alteration zones and are established on the largest scale. Ore mineralisation occurs as veins, veinlets in silicification zones or secondary mineralisation in the supergene zone (Perama epithermal system). Disseminated ore mineralization is also found in the silicification zone at Othondoto and Mavrokoryfi epithermal systems. Based on the geological environment, the type of hydrothemal alteration zones (silicification and advanced argillic alteration) and the mineral compositon of the ore (enargite- luzonite), the hydrothermal systems of Petrota graben can be referred as high sulfidation systems.